Pulse Wave Velocity: Retrospective Analysis in a Balkan Normotensive and Hypertensive Population: A Study of 9923 Patients. (January 2018) - Lovic, Dragan; Kallistratos, Manolis S.; Poulimenos, Leonidas; Skyrlas, Aggelos; Stojanov, V.; Jakovljevic, B.; Zdravkovic, M.; Koracevic, G.; Chamodraka, Eftychia; Kouremenos, Nikos; Pittaras, Andreas; Kokkinos, Peter; et al.
We compared pulse wave velocity (PWV) between hypertensive patients and control patients to identify demographics and patient characteristics related to PWV. We retrospectively analyzed 9923 participants (3105 controls and 6818 hypertensive patients) from 5 outpatient hypertensive clinics (in Serbia and Greece). Pulse wave velocity had different distribution between controls and hypertensive patients ( P < .001). The magnitude of PWV increase was related to blood pressure (BP) category (from optimal to stage III hypertension; P < .001). Even in hypertensive patients with systolic BP (SBP) <140 and/or diastolic BP (DBP) <90 mm Hg, PWV was greater than in control patients ( P < .001). Pulse wave velocity was associated with almost all baseline characteristics of hypertensive patients (body mass index [BMI], gender, age, SBP, DBP, smoking status, and heart rate; P < .001). This association remained after adjustment of PWV confounders. There were 2231 (32.7%) hypertensive patients who had reached SBP <140 mm Hg and DBP <90 mm Hg. Pulse wave velocity was increased in hypertensive patients, and the degree of PWV increase was associated with baseline BP as well as with anthropometric parameters (eg, BMI, gender, age, heart rate, and smoking status).